When Lack of Trust in the Government and in Scientists Reinforces Social Inequalities in Vaccination Against COVID-19 - Nathalie Bajos; Alexis Spire; Léna Silberzan; Antoine Sireyjol; Florence Jusot; Laurence Meyer; Jeanna-Eve Franck; Josiane Warszawski; The EpiCov study group; Nathalie Bajos; Josiane Warszawski; Guillaume Bagein; et al. (Frontiers Media S.A., 2022)
ObjectiveTo assess whether lack of trust in the government and scientists reinforces social and racial inequalities in vaccination practices.DesignA follow-up of the EpiCov random population-based cohort survey.SettingIn July 2021, in France.ParticipantsEighty-thousand nine hundred and seventy-one participants aged 18 years and more.Main Outcome MeasuresAdjusted odds ratios of COVID-19 vaccination status (received at least one dose/ intends to get vaccinated/ does not know whether to get vaccinated/refuses vaccination) were assessed using multinomial regressions to test associations with social and trust factors and to study how these two factors interacted with each other.ResultsIn all, 72.2% were vaccinated at the time of the survey. The population of unvaccinated people was younger, less educated, had lower incomes, and more often belonged to racially minoritized groups, as compared to vaccinated people. Lack of trust in the government and scientists to curb the spread of the epidemic were the factors most associated with refusing to be vaccinated: OR = 8.86 (7.13 to 11.00) for the government and OR = 9.07 (7.71 to 10.07) for scientists, compared to vaccinated people. Lack of trust was more prevalent among the poorest which consequently reinforced social inequalities in vaccination. The poorest 10% who did not trust the government reached an OR of 16.2 (11.9 to 22.0) for refusing to be vaccinated compared to the richest 10% who did.ConclusionThere is a need to develop depoliticised outreach programmes targeted at the most socially disadvantaged groups, and to design vaccination strategies conceived with people from different social and racial backgrounds to enable them to make fully informed choices.